"Big Data": A new twist to accounting. (March 2017) - Janvrin, Diane J.; Weidenmier Watson, Marcia
Highlights: Commentary introducing the Special Issue on Big Data. Highlights resources for incorporating Big Data and Data Analytics into the curriculum. Helps institutions comply with AACSB Accounting Standard 7 and Pathways Commission recommendations. Abstract: This commentary introduces the "Big Data" (hereafter, Big Data) Special Issue of the Journal of Accounting Education . We argue that while the data sets are now larger than ever before and better data analytic software is available, the primary goal of accounting has always been the same - to create and provide information to internal and external decision makers. In addition, this commentary identifies resources for incorporating Big Data into the classroom. These resources include links to free datasets, software tools, cases, and class slides. Finally, we conclude with a discussion of the articles in this Special Issue and how they fit into the existing Big Data literature.